Energy Efficient Power Allocation Scheme for Distributed Antenna Systems with Target BER Constraint - Yu, Xiangbin; Wang, Ying; Qiuming Zhu; Tao Dong; Junya Chu (China communications, 2016)
The energy efficiency（EE） of distributed antenna system with quality of service（Qo S） requirement is investigated over composite Rayleigh fading channel,where the shadow fading,path loss and Rayleigh fading are all considered. Our aim is to maximize the EE which is defined as the ratio of the transmission rate to the total consumed power subject to the maximum transmit power of each remote antenna constraint and Qo S（target BER） requirement. According to the definition of EE and using the upper bound of average EE,the optimized objective function is provided. Based on this,utilizing Karush-KuhnTucker conditions and numerical calculation,a suboptimal energy efficient power allocation（PA） scheme is developed,and the closedform expression of PA coefficients is derived. The scheme may obtain the EE performance close to the existing optimal scheme. Moreover,it has relatively lower complexity than the existing scheme because only the statistic channel information and less iteration are required. Simulation results show the presented scheme is valid and can meet the target BER requirement,and the EE can be increased as target BER requirement decreases.